FACTORS FOR IMPLEMENTING CAPITAL EXPENDITURE IN THE REGIONAL GOVERNMENT OF WEST SUMATRA PROVINCE 2018-2021 - Nofridelfi Nofridelfi; Witra Maison; Siska Yulia Defitri (Jurnal Ekonomi, 2023)
The implementation of regional autonomy provides an opportunity for regional governments to further develop the potential of their regions. To develop the potential of the region, regional governments need to increase the capital expenditure budget. The sources of funds used to finance capital expenditure consist of Original Local Government Revenue (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), and Profit Sharing Funds. This research aims to determine the effect of Original Local Government Revenue (PAD) and General Allocation Funds (DAU) on Capital Expenditures. This type of research is quantitative research with an associative (relationship) approach. The population of this research is all regencies/cities in West Sumatra. The sampling technique used was total sampling. The data used is the 2018-2021 West Sumatra Province Regency/City Regional Revenue and Expenditure Budget Realization Report. Partially, the research results show that Original Local Government Revenue (PAD) influences Capital Expenditures and General Allocation Funds (DAU) also influences Capital Expenditures. Meanwhile, simultaneously, Original Local Government Revenue (PAD) and General Allocation Funds (DAU) influence Capital Expenditures.